Export Structure Upgrading and Economic Growth in the Western Balkan Countries - Shimbov, Bojan; Alguacil, Maite; Suárez, Celestino (Taylor and Francis, 2019)
In this paper, we seek to analyze the impact that the ability to produce more sophisticated goods has on the economic performance of the Western Balkan region and to determine the factors fostering this process. To do so, we elaborate an export sophistication index, à la Hausmann. The outcomes obtained show that export sophistication has a positive and significant effect on growth in these economies. Additionally, we found that this process is driven more by the sophistication in medium-skill and technology-intensive manufactures goods rather than through sophistication in high-skill goods. Our findings also confirm that a greater participation in international production networks and a better institutional environment stimulates the upgrading of exports, and the subsequent economic growth of these economies.